Dukungan Dosen Dan Mahasiswa Stikes Maranatha Kupang Dalam Kegiatan Pekan Imunisasi Nasional (PIN) - Diah Ayu Dwi Satiti; Ninick Corea Fernandez; Ermi Lilianda Alang; Windy A.V. Fanggi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Family support for the completeness of immunization is needed so that children get complete basic immunization and as an initial step to prevent disease. Immunization is the most effective effort to provide specific immunity/immunity against Immunization Preventable Diseases (PD3I). National Immunization Week (PIN) is an immunization activity carried out simultaneously throughout Indonesia. The purpose of this community service activity is to increase understanding of immunization through campaigns to provide information, increase knowledge as an effort to improve the health of infants and toddlers. The method used is counseling in the form of health education, targeting families with toddlers 0-59 months with a total of 80 participants. Evaluation of this service activity is carried out by giving leaflets and banners with a question and answer process at the end of the activity. The results obtained from this activity were an increase in the knowledge of participants in community service activities related to understanding immunization, there was an increase that occurred before or after the activity, which was 50%.